2020
DOI: 10.1038/s41598-020-71661-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OsF3H modulates WBPH stress by alteration of phenylpropanoid pathway at a transcriptomic and metabolomic level in Oryza sativa

Abstract: The whitebacked planthopper (WBPH), has become a devastating pest for rice crops, causes serious yield losses each year, and urgently needs biological control. Here, we developed a WBPH-resistant rice cultivar by overexpressing the OsF3H gene. A genetic functional analysis of the OsF3H gene confirmed its role in facilitating flavonoid contents and have indicated that the expression of the OsF3H gene is involved in regulation of the downstream genes (OsDFR and OsFLS) of the flavonoid pathway and genes (OsSLR1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 72 publications
1
34
0
Order By: Relevance
“…The reaction was performed in a 20 μl volume containing 7 μl ddH2O, 1 μl primer, 10 μl SYBER green and 1 μl cDNA. A total sample volume of 50 μl was subjected to the following condition: initial denaturation at 94 °C for 5 mint, 40 cycle of denaturation at 94 °C for 30 s, annealing at 58 °C for 30 s, extension at 72 °C for 1 mint and final extension at 72 °C for 5 mints [ 76 , 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was performed in a 20 μl volume containing 7 μl ddH2O, 1 μl primer, 10 μl SYBER green and 1 μl cDNA. A total sample volume of 50 μl was subjected to the following condition: initial denaturation at 94 °C for 5 mint, 40 cycle of denaturation at 94 °C for 30 s, annealing at 58 °C for 30 s, extension at 72 °C for 1 mint and final extension at 72 °C for 5 mints [ 76 , 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides protective effects during plant growth, anthocyanins may also play important roles in controlling pests and maintaining plant growth. Several recent studies have reported that the increased expression levels of structural anthocyanin genes related with anthocyanin in rice plants are believed to be significant traits for enhancement of rice resistance to the white-backed planthopper [ 151 , 152 ]. A strong positive relationship between anthocyanin concentration and seedling vigor in rice has been also reported [ 153 ].…”
Section: Significant Roles Of Anthocyanin From Purple Rice In Human Hmentioning
confidence: 99%
“…In phenylpropanoid pathway, PAL, 4CL and C4H serve as the critical enzymes, of which PAL and C4H are the first and second rate-limiting enzymes [ 45 , 46 ], whereas 4CL is the key enzyme leading to the branch of phenylpropanoid pathway [ 26 ]. Phenols and flavonoids are the end products of phenylpropanoid pathway, and their accumulation are closely associated with plant resistance and senescence [ 47 , 48 , 49 , 50 , 51 ]. Lignin enhances the mechanical strength of plant cell walls and prevents microbial invasion [ 29 ], and is involved in regulation of senescence [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%